2021
DOI: 10.1111/1744-7917.12974
|View full text |Cite
|
Sign up to set email alerts
|

Early embryonic transcriptomes of Zeugodacus tau provide insight into sex determination and differentiation genes

Abstract: Zeugodacus tau (Walker) is an invasive pest. The sterile insect technique is an environment‐friendly method for pest control. Understanding the mechanism of sex determination will contribute to improving efficiency of this technique. In this study, we identified the transformer (tra) gene in Z. tau. One female‐specific and two male‐specific isoforms of tra were found in Z. tau, and the male‐specific splicing pattern of tra was found to occur 5 h after egg laying. We performed transcriptome sequencing at 1 h (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The adults were reared on an artificial diet containing 50% yeast powder and 50% sucrose. Z. tau at various life stages was cultured at 27°C ± 1°C under a 12 light: 12 dark photoperiod in cages ( Liu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The adults were reared on an artificial diet containing 50% yeast powder and 50% sucrose. Z. tau at various life stages was cultured at 27°C ± 1°C under a 12 light: 12 dark photoperiod in cages ( Liu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Cluster of Orthologous Groups of proteins (COG) analysis was performed using the OmicShare tools. 2 The Fisher’s exact test was used for the GO functional enrichment analysis of DEPs ( Liu et al, 2021 ). The Kyoto Encyclopaedia of Genes and Genomes (KEGG) 3 pathway of the target protein set was annotated using the KEGG Automatic Annotation Server (KAAS) ( Moriya et al, 2007 ; Kanehisa et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptome analyses identified sex-determination genes and cascade models in insects and animals (Liu et al, 2022a). In general, transcriptome studies provide necessary and deep knowledge into previously unknown genes of a species, specific gene functions, expression mechanisms, and species evolution in many insects (Srivastava et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In general, transcriptome studies provide necessary and deep knowledge into previously unknown genes of a species, specific gene functions, expression mechanisms, and species evolution in many insects (Srivastava et al, 2019). Recent studies demonstrated the genes involved in fecundity and ageing of social insects (Korb et al, 2021), sex determination and differentiation in Zeugodacus tau (Liu et al, 2022a), and reproduction regulation in Z. cucurbitae (Coquillett), C. capitata (Wiedemann), and Bactrocera dorsalis (Hendel) (Wu et al, 2022; Zheng et al, 2012), but not in Z. scutellata . Investigating the molecular mechanisms underlying the reproduction process is an effective tool for developing molecular level pest control strategies.…”
Section: Introductionmentioning
confidence: 99%